Fault monitoring and fault recovery control for position-moored vessels - Fang, Shaoji; Blanke, Mogens (Zielona Góra: Uniwersytet Zielonogórski)
This paper addresses fault-tolerant control for position mooring of a shuttle or floating production storage and offloading vessels. A complete framework for fault diagnosis is presented. A loss of a sub-sea mooring line buoyancy element and line breakage are given particular attention, since such failures might cause high-risk abortion of an oil-loading operation. With significant drift forces from waves, non-Gaussian elements dominate forces and the residuals designed for fault diagnosis.
Keywords: fault diagnosis; fault-tolerant control; fault recovery; position mooring; non-Gaussian change detection